Enzimas produzidas pelo fungo filamentoso Thermoascus aurantiacus - cepa PI3S3 - Caracterização bioquímica e aplicações biotecnológicas - Battisti, Juliane de Almeida (2021)
Currently, biotechnology is already of great importance, demonstrated through the expression of the ecology of various substances through the manipulation of new microorganisms, for the creation of technologies, which have health benefits. In this context, the enzymes applied in the food industries, in the maintenance of the environment, among other industries, stand out. However, genetic studies are still being carried out for improvement and new enzymatic applications. Thermoascus aurantiacus is a filamentous, thermophilic fungus and an excellent producer of a range of enzymes with biotechnological applications. Thus, the present work aimed to carry out biotechnological applications with the crude extract of the fungus that contemplate the activity of different glycosyl hydrolases, such as amylase (20.86 U mL-1 ), cellulase (10.46 U mL-1 ), invertase (1.65 U mL-1 ), pectinase (29.14 U mL-1 ) and xylanase (41.84 U mL-1 ). The application of the extract to verify the hydrolysis of the biomass showed that the enzyme complex presented on the three substrates tested, corn bagasse and corn sugar, and the highest application of reducing sugar was observed in corn corn (49.3 mg.g-1 ) after 72 hours of treatment, against 35.14 mg.g-1 for sugarcane bagasse. The enzymatic extract was applied to the animal feed, so that it was hydrolyzed, reducing 158 g of sugar per kg of feed with 12 h of treatment, treatments with 1, 3 and 6 hours increased the release of reducing sugar by 1 hour .8; 3.0 and 4.9 times, respectively, when compared to the control treatment. In vivo, no improvement was observed in the weight gain and conversion of broilers, however, in the morphology of the intestine, verified by optical microscopy, a small increase in the absorption area was observed, in addition to a subtle improvement in the metabolism of excreta. The Polygalacturo-purified enzyme, through DEAE Sephadex column, having an estimated molecular weight of 39 k molecular weight, was applied to the denim fabric (PG) generating a biopolishing of the Daje fiber and chromatographic weight by denim electron microscopy (SEM), generating in a way that such methodology can be employed employing methodologies.